Py/ExplorReg: Exploration of Transcriptome for Potential Regulon Structure Detection - Janigová, Patrícia; Weckwerth, Wolfram; Schwarzerová, Jana (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
This study introduces Py/ExplorReg, a tool designed for exploring transcriptomic landscapes and identifying potential regulon structures, with a particular focus on its utility in the context of Arabidopsis thaliana research. Developed using Python, Py/ExplorReg demonstrates its effectiveness in identifying potential regulons through a pioneering approach rooted in the analysis of gene expression data. Leveraging publicly available datasets from the EMBL-EBI project PRJNA779072, this case study highlights its adaptability to Arabidopsis thaliana datasets.
Keywords: Arabidopsis thaliana; Gene expression analysis; Regulon; Transcription units